2020
DOI: 10.7759/cureus.10723
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery Anomalies in Tetralogy of Fallot Patients Undergoing CT Angiography at a Tertiary Care Hospital

Abstract: Background The aim of this study was to determine the frequency of coronary artery anomalies (CAAs) in Tetralogy of Fallot (TOF) patients undergoing computed tomography (CT)-angiography in a tertiary care hospital. Methodology In this observational study, we included consecutive TOF patients undergoing CT-angiography without prior history of cardiac surgery or congenital heart disease. CAAs were defined based on either origin or course of the artery. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…This is in concordance with the recently published meta‐analysis that estimated the prevalence of anomalous coronary arteries to be 6% based on 6956 patients from combined studies 7 . Only a few studies utilized CT angiography for the detection of anomalous coronary arteries in TOF and these studies reported a prevalence of 8.5% and 3.6% respectively 3,10 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is in concordance with the recently published meta‐analysis that estimated the prevalence of anomalous coronary arteries to be 6% based on 6956 patients from combined studies 7 . Only a few studies utilized CT angiography for the detection of anomalous coronary arteries in TOF and these studies reported a prevalence of 8.5% and 3.6% respectively 3,10 …”
Section: Discussionsupporting
confidence: 87%
“…7 Only a few studies utilized CT angiography for the detection of anomalous coronary arteries in TOF and these studies reported a prevalence of 8.5% and 3.6% respectively. 3,10 In the present study, the incidence of anomalous coronary arteries crossing anterior to RVOT in TOF patients was 63.29%…”
Section: Incidence Of Various Anomalies Of Coronary Arteries In Tofmentioning
confidence: 45%
See 2 more Smart Citations
“…The most common test is an echocardiogram [4], an ultrasound of the heart that can show problems with the heart structure and how well the heart is working with this defect. Recently, computed tomography (CT) has shown its success in the differential diagnosis of TOF [5], since it can provide detailed images of many types of cardiovascular issue; besides, computed tomography (CT) can be performed even if the subject has an implanted medical device, unlike magnetic resonance imaging (MRI) [6].…”
Section: Introductionmentioning
confidence: 99%